A Brief Overview on the Recent Trends of English Literature - Ben J. Milton; Manikandaboopathy (AG Volumes, 2022)
Culture, values, beliefs, and traditions are all reflected in the work of literature, which is a useful ability to have. Many people have been able to get a better understanding of the past and the present via this medium. Literature has the power to move people to explore their imaginations, discover new things, and contemplate their place in the world. Literature may be used to reflect on the world around us, but it can also serve as a gateway to new ideas and concepts. It has long been used as a technique of communicating with other people all over the globe in a language that is today understood by the general public. For this topic, the focus is on literary trends and how they have influenced the development of English literature. A comprehensive literature review using a guided literature search was used to gather the data for this investigation. Using internet-connected devices to link people across the world has led to a wide range of modern-day literary trends, according to the findings of this study. Allows for diverse viewpoints on injustices, murderous conquests, and political unrest. The internet, e-books, and social media are driving a shift in the way literature is created, perceived, and read, displacing the linear, lonely, and closed reading experience. Topics include the "6-word book," blogs, and hypertext. According to the findings of this research, globalization and the internet have had a profound impact on literature, and there is a direct link between literary and society influence.